2000
DOI: 10.1002/1529-0131(200009)43:9<1994::aid-anr10>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine induces apoptosis in activated human lymphoblasts: A mechanism supporting the induction of drug‐induced lupus erythematosus?

Abstract: These data suggest that chlorpromazine mediates apoptosis in human lymphoblasts through specific activation of intracellular proapoptotic signaling cascades. This mechanism might lead to an unsynchronized inflow of apoptotic break-down products and thereby to the induction of (auto)immunity against nuclear components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…It is intriguing to speculate that the different lymphoblast responses to the anti‐apoptotic γc‐chain cytokines might contribute to the induction and/or perpetuation of autoimmunity. An increased rate of apoptosis could lead to an overflow of the phagocytic system with apoptotic cell bodies and contribute to the induction of autoimmunity 3, 7, 27, 28. This concept is strongly supported by the findings of van Deventer and coworkers 29, 30 who recently published observations of a strong induction of apoptosis in activated lamina propria lymphocytes after the treatment of Crohn's patients with infliximab.…”
Section: Discussionmentioning
confidence: 89%
“…It is intriguing to speculate that the different lymphoblast responses to the anti‐apoptotic γc‐chain cytokines might contribute to the induction and/or perpetuation of autoimmunity. An increased rate of apoptosis could lead to an overflow of the phagocytic system with apoptotic cell bodies and contribute to the induction of autoimmunity 3, 7, 27, 28. This concept is strongly supported by the findings of van Deventer and coworkers 29, 30 who recently published observations of a strong induction of apoptosis in activated lamina propria lymphocytes after the treatment of Crohn's patients with infliximab.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, CPZ has been shown to affect the activities of a variety of T lymphocytes in vitro (17,19,21), although these inhibitory effects require concentrations of CPZ which are beyond those clinically relevant (i.e., in excess of 1 mg/liter) or fairly close to the highest concentration of CPZ in plasma that might result from its aggressive use (Ն0.5 mg/liter). Our previous study (32) and the present study show that an in vitro concentration of 0.1 mg of either CPZ or TZ per liter, which is equivalent to that anticipated to be present in the plasma of a patient treated with either phenothiazine, has no significant toxicity against macrophages or alpha-beta TCR ϩ , gamma-delta TCR ϩ , or CD14 ϩ macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that chlorpromazine induces apoptosis in human lymphoblasts by stimulating proapoptotic signaling pathways [69]. This is in contrast to the mechanism proposed for TNFa induced autoimmunity, in which case a defect in apoptosis leads to the failure to eliminate autoreactive B and T cells, leading to a breakdown of central or peripheral tolerance.…”
Section: Other Agents and Autoimmunitymentioning
confidence: 92%